The Impact of Financial Literacy, Managerial Ability, and Social Capital on Entrepreneurial Success with Business Strategy as an Intervening Variable - Sari, Kadek Kartika; Suhardi, Suhardi; Rejeki, Nadia Sri (Economic: Journal Economic and Business, 2025)
This study aims to analyze the influence of financial literacy, managerial skills, and social capital on entrepreneurial success, with business strategy as a mediating variable. Respondents in this study were 135 Micro, Small, and Medium Enterprises (MSMEs) that have been operating for at least two years. The research method uses a quantitative approach with the Partial Least Square - Structural Equation Modeling (PLS-SEM) analysis technique through SmartPLS 4.0 software. The results of the study indicate that financial literacy and social capital have a significant effect on entrepreneurial success, while managerial skills do not have a significant effect. The three independent variables do not show a significant effect on business strategy. However, business strategy is proven to have a significant effect on entrepreneurial success, which confirms its role as a mediating variable. These findings emphasize the importance of strengthening financial literacy and social capital in supporting business success, as well as the need to increase managerial capacity to optimize the formulation of adaptive and sustainable business strategies.